Screening and Relative Quantification of Migration from Novel Thermoplastic Starch and PBAT Blend Packaging - Phanwipa Wongphan; Elena Canellas; Cristina Nerín; Carlos Estremera; Nathdanai Harnkarnsujarit; Paula Vera (Foods)
A novel biodegradable food packaging material based on cassava thermoplastic starch (TPS) and polybutylene adipate terephthalate (PBAT) blends containing food preservatives was successfully developed using blown-film extrusion. This active packaging is designed to enhance the appearance, taste, and color of food products, while delaying quality deterioration. However, the incorporation of food preservatives directly influences consumer perception, as well as health and safety concerns. Therefore, this research aims to assess the risks associated with both intentionally added substances (IAS) and non-intentionally added substances (NIAS) present in the developed active packaging. The migration of both intentionally and non-intentionally added substances (IAS and NIAS) was evaluated using gas chromatography–mass spectrometry (GC-MS) and ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS). Fifteen different volatile compounds were detected, with the primary compound identified as 1,6-dioxacyclododecane-7,12-dione, originating from the PBAT component. This compound, along with others, resulted from the polymerization of adipic acid, terephthalic acid, and butanediol, forming linear and cyclic PBAT oligomers. Migration experiments were conducted using three food simulants—95% ethanol, 10% ethanol, and 3% acetic acid—over a period of 10 days at 60 °C. No migration above the detection limits of the analytical methods was observed for 3% acetic acid and 10% ethanol. However, migration studies with 95% ethanol revealed the presence of new compounds formed through interactions between the simulant and PBAT monomers or oligomers, indicating the packaging’s sensitivity to high-polarity food simulants. Nevertheless, the levels of these migrated compounds remained below the regulatory migration limits.